2012
DOI: 10.1148/radiol.12112351
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Perifissural Nodules on CT Scans: Rapid Growth Is Not a Predictor of Malignancy

Abstract: PFNs are frequently found at CT scans for lung cancer. They can show growth rates in the range of malignant nodules, but none of the PFNs in the present study turned out to be malignant. Recognition of PFNs can reduce the number of follow-up examinations required for the workup of suspicious nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
141
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 16 publications
7
141
1
6
Order By: Relevance
“…n.m. not measured nodules have very low probability of malignancy [16,25]. De Hoop et al showed that perifissural nodules are rarely malignant, even in case of rapid growth [26]. In this study, we also found that in 2 years after baseline, none of the downward adjusted nodules turned out to be lung cancer.…”
Section: Discussionsupporting
confidence: 66%
“…n.m. not measured nodules have very low probability of malignancy [16,25]. De Hoop et al showed that perifissural nodules are rarely malignant, even in case of rapid growth [26]. In this study, we also found that in 2 years after baseline, none of the downward adjusted nodules turned out to be lung cancer.…”
Section: Discussionsupporting
confidence: 66%
“…When small nodules have a perifissural or other juxtapleural location and a morphology consistent with an intrapulmonary lymph node, follow-up CT is not recommended, even if the average dimension exceeds 6 mm. In one study of patients in the NELSON Lung Cancer Screening Trial, 20% of nodules were classified as perifissural, and 16% of these grew during the study; however, none were malignant (94). However, perifissural or juxtapleural location does not in itself reliably indicate benignancy, and the specific nodule morphology must be considered (95,96).…”
Section: Perifissural Nodulesmentioning
confidence: 99%
“…These nodules probably correspond to perifissural lymph nodes and represented 20% of the nodules found at baseline screening in the NELSON study, a result that is far from insignificant [21].…”
Section: How To Reduce False-positive Computed Tomography Resultsmentioning
confidence: 91%
“…Nodules classified as perifissural can be considered benign, as proven by long term follow-up, even in the case of rapid growth in high-risk patients [20,21]. These nodules probably correspond to perifissural lymph nodes and represented 20% of the nodules found at baseline screening in the NELSON study, a result that is far from insignificant [21].…”
Section: How To Reduce False-positive Computed Tomography Resultsmentioning
confidence: 93%